The effect of sand on the mechanical characteristics of gypsum-lime mortars for heritage buildings - M abed, Duaa; M abed, Jasim; Al-Saffar, Zaid Hazim; Putra Jaya, Ramadhansyah (IOP Publishing, 2024)
The endurance and preservation of historical buildings greatly depend on the integration of lime into the mortar used for masonry linings. Therefore, conducting mechanical assessments of existing and restoration mortars is crucial to ensure their compatibility and prevent potential issues. This article emphasizes the role of sand in enhancing the efficiency and resilience of gypsum-lime mortars by examining how it influences on their mechanical properties. The main aim of this research is to provide practical guidance for the sustainable restoration and conservation of historical edifices. The study examines the mechanical attributes of gypsum-lime mortars for restoring historical structures, with a specific focus on evaluating the impact of different sand proportions (10%, 15%, and 20% by gypsum volume). Moreover, the results were scrutinized to comprehend the compositions, structural features, and compressive strength. Among the six mortar blends, the addition of 15% sand was identified as the most effective augmentation to gypsum-lime, demonstrating comparable workability. Furthermore, this proportion exhibited improved compressive and flexural strengths on the seventh day compared to pure gypsum-lime. This highlights the potential economic application and further enhancement of this locally sourced product in various finishing applications. Notably, gypsum-lime mortar infused with 15% sand exhibited optimal structural properties, particularly in terms of compressive strength.